2016
DOI: 10.1016/j.jprot.2016.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic changes in human lung epithelial cells (A549) in response to carbon black and titanium dioxide exposures

Abstract: In this study we have shown that toxicoproteomics is a sensitive and informative method to resolve the toxicity characteristics of particles with different physicochemical properties. This approach can be useful in the investigation of molecular mechanisms underpinning cellular cytotoxic responses elicited by particle exposures. Thus, the toxicoproteomic approach can be valuable in assessing the risk associated with particle exposures in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…Changes in the proteome of A549 cells after 24 h of exposure to CR and MI particles were assessed via 2D‐GE as described previously (Vuong et al ., ,b). The results presented in Supporting information Table S1 revealed that the expressions of 49 protein spots were significantly affected by both CR and MI (two‐way ANOVA: Treatment × Dose interaction, Treatment or Dose main effects, P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Changes in the proteome of A549 cells after 24 h of exposure to CR and MI particles were assessed via 2D‐GE as described previously (Vuong et al ., ,b). The results presented in Supporting information Table S1 revealed that the expressions of 49 protein spots were significantly affected by both CR and MI (two‐way ANOVA: Treatment × Dose interaction, Treatment or Dose main effects, P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Total protein from the A549 cells (control and particle‐exposed) was extracted and examined by two‐dimensional gel electrophoresis (2D‐GE) as previously described (Vuong et al ., ,b). Following electrophoresis, the gel was washed for 30 min in water, stained in BioSafeCoomassie Blue (Bio‐Rad) overnight (16–20 h), destained twice in water (20 min) and then imaged with a standard scanner.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a detailed proteomic investigation to assess the molecular mechanisms delineating the toxic effects of EHC-93 as a whole (total) or separated fractions (i.e., insoluble and soluble) has not been conducted. In our recent studies, we demonstrated that in vitro toxicoproteomics is an approach that is capable of distinguishing the pathways associated with cytotoxic effects of respirable particles that are different in physicochemical properties such as carbon black and titanium dioxide [ 62 , 63 ]. Furthermore, we also showed that our in vitro toxicoproteomic approach was capable of differentiating the effects of particles that were identical in chemical formula (SiO 2 ) but differed in physical properties such as cristobalite and α-quartz [ 61 ].…”
Section: Introductionmentioning
confidence: 99%